Perturbation effect of stellar spots on light curves of gravitational microlensing - S Sajadian; M Rashidi (Iranian Journal of Physics Research, 2021)
One of the advantages of observations of gravitational microlensing is stellar spots detection.  Our aim ‎in this paper is to study and characterize the perturbations due to stellar spots on the microlensing ‎light curves. Considering a suitable formalism for the stellar spots, we simulate the microlensing of ‎spotted source stars. One of the effects of a spot on stellar light curve is the local demagnification (where ‎the lens is crossing the stellar spot) and it causes asymmetric perturbations on the light curve. The ‎spots that locate at the source center after projection make larger and deeper perturbations than the ‎spots locate the stellar limbs. In caustic crossing binary microlensing events, the typical-size spot-‎induced perturbations mostly make (more than 40‏‎ percent) the relative deviations larger than ‎‏5‏‎. This ‎fraction is bigger for single lensing events‎‎‎.‎